1993
DOI: 10.1073/pnas.90.23.11287
|View full text |Cite
|
Sign up to set email alerts
|

Galanin-receptor ligand M40 peptide distinguishes between putative galanin-receptor subtypes.

Abstract: The glanin-receptor Hlgand M40 [galanin-(1-12)-Pro3-(Ala-Leu)2-AIa amide] binds with high affinity to galanin-binding sites in hippocampal, hypothalamic, and spinal cord membranes and in membranes from Rin m5F rat insulinoma cells . Receptor autoradlographic studies show that M40 (1 "M) displaces galanin from binding sites in the hippocampus, hypothalamus, and spinal cord. In the brain, M40 acts as a potent galanin-receptor antagonist: M40, in doses comparable to that of galanin, antagonizes the stimulatory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 33 publications
1
77
1
1
Order By: Relevance
“…Bilateral microinjections of vehicle, or the galanin antagonist M40 (0.2 or 1.0 nmole per side) were made into the BSTL. These doses of M40 were shown to be effective in previous studies by us (Khoshbouei et al 2001) and by others (Crawley et al 1993;McDonald and Crawley 1996). All drugs were injected in a volume of 0.2 l at a rate of 0.2 l/min.…”
Section: Experiments 1: Modulation Of Behavioral Reactivity To Acute Smentioning
confidence: 61%
See 3 more Smart Citations
“…Bilateral microinjections of vehicle, or the galanin antagonist M40 (0.2 or 1.0 nmole per side) were made into the BSTL. These doses of M40 were shown to be effective in previous studies by us (Khoshbouei et al 2001) and by others (Crawley et al 1993;McDonald and Crawley 1996). All drugs were injected in a volume of 0.2 l at a rate of 0.2 l/min.…”
Section: Experiments 1: Modulation Of Behavioral Reactivity To Acute Smentioning
confidence: 61%
“…The galanin antagonist M40 (Bartfai et al 1993) has been shown in vivo to block the effects of exogenous galanin administration on memory tasks (McDonald and Crawley 1996) and food intake (reviewed in Crawley 1999). Thus, in this experiment, we administered M40 directly into BSTL to address the potential role of endogenous galanin in modulating behavioral and neuroendocrine responses to acute stress.…”
Section: The Neuropeptide Galanin Has Been Identified As a Possible Nmentioning
confidence: 99%
See 2 more Smart Citations
“…To clone additional members of the galanin receptor family, we used an expression cloning strategy based on the hypothesis that there were multiple galanin receptors present in hypothalamus (17,29). A randomly primed cDNA expression library was constructed from rat hypothalamus and screened in pools by radioligand binding/photoemulsion detection using 125 IpGAL.…”
Section: Resultsmentioning
confidence: 99%